MicroRNAs as Regulators and Biomarkers of Platelet Function and Activity in Coronary Artery Disease - Stojkovic, Stefan; Nossent, Anne Yaël; Haller, Paul; Jäger, Bernhard; Vargas, Kris G.; Wojta, Johann; Huber, Kurt (Thrombosis and Haemostasis, 2019)
Microribonucleic acids (miRs) are small, noncoding ribonucleic acids (RNAs), which play an important role in the regulation of platelet function and activity. Several studies proposed a mechanistic role of platelet-related miRs in the pathophysiology of coronary artery disease (CAD) and atherothrombosis. Circulating, platelet-related miRs have been proposed as diagnostic, prognostic, as well as treatment response biomarkers in CAD and acute coronary syndrome (ACS). In this review, we summarize recent studies on the role of platelet-related miRs in the regulation of platelet function and activity. Furthermore, we review the studies investigating the role of platelet-related miRs as biomarkers in patients with CAD and ACS.
Keywords: microRNA; platelet function; coronary artery disease; acute myocardial infarction; acute coronary syndrome